2013
DOI: 10.1109/tbme.2013.2272601
|View full text |Cite
|
Sign up to set email alerts
|

Towards BirthAlert—A Clinical Device Intended for Early Preterm Birth Detection

Abstract: Preterm birth causes 1 million infant deaths worldwide every year, making it the leading cause of infant mortality. Existing diagnostic tests such as transvaginal ultrasound or fetal fibronectin either cannot determine if preterm birth will occur in the future or can only predict the occurrence once cervical shortening has begun, at which point it is too late to reverse the accelerated parturition process. Using iterative and rapid prototyping techniques, we have developed an intravaginal proof-of-concept devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Previous works published in the literature (Avis et al, 1997;Etemadi et al, 2013;Gandhi et al 2006a;2006b;Hoe et al, 2004;O'Connell et al, 2000) produced results in line with those reported here. However, none of them include an equivalent circuit for the cervical tissue, as it is done here.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous works published in the literature (Avis et al, 1997;Etemadi et al, 2013;Gandhi et al 2006a;2006b;Hoe et al, 2004;O'Connell et al, 2000) produced results in line with those reported here. However, none of them include an equivalent circuit for the cervical tissue, as it is done here.…”
Section: Discussionsupporting
confidence: 92%
“…2018 June;34(2): 110-114 111/114 disassembles, together with the cervical tissue hydration (Cunningham et al, 2010). Currently, these cervical tissue microstructural changes can be inferred by using two techniques: light-induced fluorescence spectroscopy (LIF) and electrical impedance spectroscopy (EIS) (Etemadi et al, 2013). The former is based on the auto fluorescent properties of the collagen cross-links; and the latter is based on the electrical impedance characteristics of the cervical tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific use of this device is described in Etemadi et al 12,13 . The mold used to create the intravaginal probe was fabricated from ABS430 material using a Dimension uPrint Plus 3D printer.…”
Section: Representative Resultsmentioning
confidence: 99%